Marius Barbeau's photographic collection : The Nass River - Barbeau, Marius, 1883-1969 (Book collections on Project MUSE., 1988)
Catalogue of archival photographs taken by Marius Barbeau between 1927 and 1929, of the Nishga Indian culture of the Nass River area in northern British Columbia. Includes material culture, portraits, totem poles and index of proper names, negative numbers by subject and negative numbers chronologically.